Combining CD3/GD2 bispecific T cell engager with human Vγ9Vδ2 T cells facilitates neuroblastoma cell targeting and killing in vitro - Kuntida Kitidee; Sumet Amonyingcharoen; Sarinthip Preedagasamzin; Korakot Atjanasuppat; Piamsiri Sawaisorn; Pornprapa Srimorkun; Sawang Petvises; Wanpen Chaicumpa; Suparerk Borwornpinyo; Usanarat Anurathapan; Suradej Hongeng (PLoS ONE, 2025)
Cancer immunotherapy, particularly T cell–based therapies, is considered to have strong potential for treating various types of cancer. A promising approach that has emerged is the use of γδ T cell-based strategies for cancer treatment. Neuroblastoma (NB), a solid tumor frequently found in childhood, is one of the more intriguing targets for immunotherapy. In this study, we report an alternative immunotherapy method for treating neuroblastoma by combining bispecific antibody with human Vγ9Vδ2 T cells. Initially, we screened for human scFv against CD3 epsilon using phage panning technology. Human scFv CD3 clone 18 demonstrated the highest ability to bind CD3 epsilon in an indirect ELISA assay. Consequently, we selected human scFv CD3 clone 18 to create a bispecific T cell engager antibody targeting both CD3 and disialoganglioside (GD2), called CD3/GD2 BiTE. This bispecific antibody was composed of human scFv CD3 clone 18 (VH-VL) and mouse scFv GD2 (VL-VH), linked by a flexible peptide linker. The interleukin-2 signal sequence and polyhistidine tag were added at the N- and C-termini for protein secretion and purification, respectively. CD3/GD2 BiTE was transiently produced in a mammalian cell expression system, which provided both high yield and quality. The CD3/GD2 BiTE folded naturally into a compact monomeric structure. Cell-based binding activity assays demonstrated that CD3/GD2 BiTE specifically binds to its target antigens on CD3-positive Jurkat cells and GD2-positive SH-SY5Y cells, but did not react with CD3-negative Raji cells and GD2-negative SK-N-SH cells. In subsequent in vitro experiments, the cytotoxicity of CD3/GD2 BiTE combined with human Vγ9Vδ2 T cells against neuroblastoma cells was evaluated. Human Vγ9Vδ2 T cells were primed with CD3/GD2 BiTE to improve the binding specificity and avidity against neuroblastoma cell lines before adding into SH-SY5Y cells. At concentrations of 180 and 360 nM, the CD3/GD2 BiTE significantly enhanced the killing ability of human Vγ9Vδ2 T cells against SH-SY5Y cells at an E:T ratio of 1:1. Moreover, CD3/GD BiTE armed with human Vγ9Vδ2 T cells enabled the killing of neuroblastoma cells using five- to ten-times fewer effector cells. The combination of CD3/GD2 BiTE and human Vγ9Vδ2 T cells also exhibited cytotoxic activity against a three-dimensional tumor spheroid model of SH-SY5Y GFP at an E:T ratio of 1:1. Consequently, CD3/GD2 BiTE enhances tumor-targeting and cytotoxic abilities of human Vγ9Vδ2 T cells against neuroblastoma cells in both two-dimensional and three-dimensional cell cultures. These results suggest that the combination of CD3/GD2 BiTE and human Vγ9Vδ2 T cells could represent an alternative immunotherapy strategy for treating neuroblastoma patients in the future.